2007
DOI: 10.1038/sj.jcbfm.9600324
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cell Infiltration after Endothelin-1-Induced Cerebral Ischemia: Histochemical and Myeloperoxidase Correlation with Temporal Changes in Brain Injury

Abstract: Accumulation of neutrophils in brain after transient focal stroke remains controversial with some studies showing neutrophils to be deleterious, whereas others suggest neutrophils do not contribute to ischemic injury. Myeloperoxidase (MPO) has been used extensively as a marker for quantifying neutrophil accumulation, but is an indirect method and does not detect neutrophils alone. To elucidate the interaction of macrophages in the neutrophil inflammatory response, we conducted double-label immunofluorescence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
100
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 97 publications
(196 reference statements)
12
100
2
2
Order By: Relevance
“…We found that MPO, a key enzyme secreted in the inflammatory response to tissue injury, is widely distributed in the ischemic tissues, and correlated positively with infarct size. The peak level of MPO activity, determined by activation of the MPO-sensing agent in vivo and confirmed by MPO activity assays and qRT-PCR analyses, occurred on day 3 after ischemia in our model, similar to previous ex vivo findings (5). Both neutrophils and macrophages/microglia contribute to secrete MPO in the ischemic brain, although neutrophils peak earlier (days 1-3), whereas macrophages/microglia are most abundant later (days 3-7).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We found that MPO, a key enzyme secreted in the inflammatory response to tissue injury, is widely distributed in the ischemic tissues, and correlated positively with infarct size. The peak level of MPO activity, determined by activation of the MPO-sensing agent in vivo and confirmed by MPO activity assays and qRT-PCR analyses, occurred on day 3 after ischemia in our model, similar to previous ex vivo findings (5). Both neutrophils and macrophages/microglia contribute to secrete MPO in the ischemic brain, although neutrophils peak earlier (days 1-3), whereas macrophages/microglia are most abundant later (days 3-7).…”
Section: Discussionsupporting
confidence: 74%
“…Inflammation in stroke has been traditionally identified on histopathology as neutrophil infiltration, which correlates positively with ischemic damage (5). Myeloperoxidase (MPO) is the most abundant component in azurophilic granules in neutrophils and has often been used as a histopathological marker for neutrophils (6).…”
mentioning
confidence: 99%
“…29 Neutrophil accumulation peaked at 3 days and persisted for at least 15 days. 8 The present human data are consistent with these results: neonates with abnormal neurologic outcome had significantly higher peripheral WBC and ANC by 12 to 24 h of life compared to neonates with good long-term neurologic outcome. Because neutrophils produce reactive and toxic metabolites such as reactive oxygen species and hypochlorous acid via two enzymes, membrane-associated nicotinamide adenine dinucleotide phosphate (NADPH) oxidase and myeloperoxidase, respectively, continued and prolonged accumulation of neutrophils in the injured area exacerbates hypoxic-ischemic-induced brain injury.…”
supporting
confidence: 81%
“…5 Hypoxia increases white blood cell (WBC) production and the number of circulating neutrophils, 6 while cytokines increase vascular permeability 7 and upregulate expression of intercellular adhesion molecules (ICAM), mediators that induce migration of leukocytes and promote local inflammatory reactions. 8 In addition, cytokines increase the affinity of neutrophil integrins to ICAMs 8,9 promoting transendothelial migration. 7,10,11 Inflammation-induced cell injury occurs due to the 'oxidation burst' that involves neutrophil production of reactive and toxic metabolites such as hydrogen peroxide, superoxide anion and hypochlorous acid.…”
Section: Introductionmentioning
confidence: 99%
“…8 These infiltrating cells include neutrophils, monocytes, macrophages, dendritic cells, T and B lymphocytes, and natural killer cells. 8 For example, clinical and experimental data suggest that neutrophils are a key immune cell to enter the brain after ischemia, and neutrophil number correlates with the severity of an ischemic lesion, 9,10 although there is some controversy as to whether this is an early event or is delayed by up to 3 days. 8 It is also remains controversial as to whether neutrophils contribute directly to secondary brain damage or are merely bystanders that mainly assist in promoting tissue repair and recovery.…”
Section: Introductionmentioning
confidence: 99%